Diverse Coordinative Zinc Complexes Containing Amido-Pyridinate Ligands: Structural and Catalytic Studies - Chen, Ming-Tsz; Chen, Yu-Yang; Li, Guan-Lin; Chen, Chi-Tien (Frontiers in Chemistry, 2019)
In this work, zinc complexes containing amidopyridinate ligands substituted with different pendant arms have been described. Treatment of ligand precursors with ZnEt2 at a 1:1 ratio in THF yields zinc ethyl complexes (PyNC1Py)2(ZnEt)2 (1) and (PyNC2NMe2)2(ZnEt)2 (2), respectively. Complexes 1 and 2 show the same geometry as a distorted tetrahedron, but adopt different coordination behaviors supported by the ligands. Complex 1 represents a rare and a non-centrosymmetric mode, which the amido group bridges two zinc centers to form a six-membered ring. However, complex 2 shows a centrosymmetric mode, which the pyridine group links to the zinc centers to form an eight-membered ring. Recrystallization of complex 2 gives an additional complex (PyNC2NMe2)4Zn3(μ3-O) (3). We attempted to prepare zinc benzyl oxide complexes but afforded only a self-assembly cubane complex Zn7Et6(OBn)8(4). All molecular structures 1–4 are characterized depending on both single-crystal X-ray and spectroscopic data. Furthermore, their catalytic properties toward the ring opening polymerization of ε-caprolactone and L-lactide, using benzyl alcohol as the initiation reagent, are under investigation.